Kan magten fornuftbestemme religionen? - Johansen, Niels Mattsson; Karlsen, Mads Peter (Dansk Teologisk Tidsskrift, 2011)
This review presents a short introduction to the main problem addressed in Lars Albinus’ doctoral thesis Religion, Power and Communication ensued by a critical discussion of the following three central issues at stake in the thesis. First, the thesis’ ambitious attempt to produce a dialectical reading of Foucault’s analytics of power and Habermas’s theory of communicative action is evaluated. Then, after a compressed outline of the solution that the thesis proposes to its main problem, this solution is discussed. And last, the notion of a post-metaphysical non-authoritative God indicated in the thesis is briefly considered.